A Novel Rubber Composite Sleeper-Deformation-Prediction Model Based on Response Surface Method (RSM) and Machine Learning (ML) Techniques - Abdulmumin Ahmed Shuaibu; Zhiping Zeng; Ibrahim Hayatu Hassan; Wang Weidong; Hassan Suleiman Otuoze; Suleiman Abdulhakeem; Bushrah Baba Abdulrahman (Journal of Techniques)
Rubber composite sleepers can experience significant temperature variations in service, causing temperature-induced deformation. Real-time monitoring of this deformation is crucial for operational safety and maintenance; however, it is costly, time-consuming, and requires substantial resources and personnel.